Annual cycle and inter-annual variability of gross primary production and ecosystem respiration in a floodprone river during a 15-year period - UEHLINGER, URS (Freshwater biology, 2006)
Summary 1. Temporal variation in ecosystem metabolism over a 15‐year period (1986–2000) was evaluated in a seventh order channelised gravel bed river (mean annual discharge 48.7 m3 s−1) of the Swiss Plateau. The river is subject to frequent disturbance by bed‐moving spates. Daily integrals of gross primary production (GPP) and ecosystem respiration (ER) were calculated based on single‐station diel oxygen curves. 2. Seasonal decomposition of the time series of monthly metabolism rates showed that approximately 50% of the variation of GPP and ER can be attributed to season. Annual GPP averaged 5.0 ± 0.6 g O2 m−2 day−1 and showed no long‐term trend. 3. Ecosystem respiration, averaging 6.2 ± 1.4 g O2 m−2 day−1, declined from 8.8 to 4.1 g O2 m−2 day−1 during the 15‐year period. This significant trend paralleled a decline in nitrate and soluble reactive phosphorus concentrations, and the biochemical oxygen demand discharged by sewage treatment facilities upstream of the study reach. The ratio of GPP to ER (P/R) increased from 0.53 to about 1 as consequence of ER reduction. 4. Bed moving spates reduced GPP by 49% and ER by 19%. Postspate recovery of GPP was rapid between spring and autumn and slow during winter. Recovery of ER lacked any seasonal pattern. Annual patterns of daily GPP and to a minor extent of daily ER can be described as a sequence of recovery periods frequently truncated by spates. 5. The study showed that disturbance by frequent bed‐moving spates resulted in major stochastic variation in GPP and ER but annual patterns were still characterised by a distinct seasonal cycle. It also became evident that stream metabolism is a suitable method to assess effects of gradual changes in water quality.